Characterization of Degradation in Nickel Impregnated Scandia-Stabilize Zirconia Electrodes during Isothermal Annealing. Issue 9 (11th July 2017) - Chen, Jingyi; Bertei, Antonio; Ruiz-Trejo, Enrique; Atkinson, Alan; Brandon, Nigel P.
Abstract : This study investigates the stability of nickel-impregnated scandia-stabilize zirconia composite electrodes during isothermal annealing at temperatures from 600 to 950°C in a humidified hydrogen atmosphere (3 vol % water vapor). Typically an initial rapid degradation of the electrode during the first 17 h of annealing is revealed by both an increase in polarization resistance and a fall in electronic conductivity. Secondary electron images show a shift in nickel particle size toward larger values after 50 h of annealing. The declining electrochemical performance is hence attributed to nickel coarsening at elevated temperatures. Nickel coarsening has two microstructural effects: breaking up nickel percolation; and reducing the density of triple phase boundaries. Their impact on electrode area specific resistance is explored using a physical model of electrode performance which relates the macroscopic electrochemical performance to measurable microstructural parameters.